Social Work Students Sharing Practice Learning Experiences: Critical Reflection as Process and Method. Issue 4 (25th March 2021) - Walker, Jane; Gant, Valerie
Abstract : This paper offers a commentary regarding the centrality of critical reflection in social work before discussing a research project drawing on a sample of ten social work students as they approached the end of their social work training in one English university. The original intention of the research was to focus solely on students' perceptions of critical reflection, but when using a more reflexive approach, we identified that participants utilised the focus groups as an opportunity to discuss their practice learning experiences per se before considering and discussing critical reflection. Most students were placed in child protection social work teams and discussed how they felt unprepared for such a fast-paced and stressful environment. Participants felt that the expectations some practitioners had of students were unrealistic, and not always commensurate with the Professional Capabilities Framework. Students highlighted the use of practice scenarios in developing their knowledge and skills particularly when considering their application of critical reflection. This study highlights the significance of adequate preparation for practice and argues for a more focussed agenda for future research exploring the culture of learning, including those factors that inhibit students sharing their concerns as well as the training needs of educators.